"Never good enough." A situated understanding of the impact of digitalization on citizens living in a low socioeconomic position. Issue 4 (18th July 2022) - Goedhart, Nicole S.; Verdonk, Petra; Dedding, Christine
Abstract: Digital inequality is a critical issue in our knowledge economy. Often digital inequality is framed as a problem that only older people encounter. This rather stereotypical portrayal can result in improvised and unsuccessful policy actions. The goal of the article is to take the experiences of citizens who never or seldom use information and communication technology as a point of departure to show the impact and outcomes of digitalization on the lives of people with a low socioeconomic position (LSEP) and across different intersections, such as gender, poverty, ethnicity, and age. The results of this qualitative study emphasize that not being able to use the Internet negatively impacts feelings of belonging and self‐confidence. Citizens need to invest continually in new or different equipment and in skills to keep up. Opportunities to invest are shaped at the nexus of gender, class, educational level, and occupational status. Therefore, simply training people in particular digital skills is insufficient. We show that the complexity of digital inequality and its interrelatedness with social inequalities along lines of class, age, gender, and ethnicity demand that policy and practices address digital inequality across the entire scope. 摘要: 数字不平等是知识经济中的关键问题。通常，数字不平等被定义为一个只有老年人才会遇到的问题。这种相当刻板的描绘能导致毫无准备且失败的政策行动。本文旨在以"从未使用或很少使用信息通信技术（ICT）的公民经验"为出发点，展示数字化在不同交叉（例如性别、贫困、族群性和年龄）的情况下对社会经济地位低（LSEP）的人民生活产生的影响和结果。本定性研究的结果强调，不能使用互联网会对归属感和自信心产生负面影响。公民需要对新的或不同的设备和技能持续投入精力，以期跟上（网络）发展。投资机会受性别、阶级、教育水平和职业地位的影响。在应对数字不平等时，仅仅对人们进行特定数字技能培训是不够的。我们表明，数字不平等的复杂性及其与阶级、年龄、性别和族群性方面的社会不平等的相互关联性，要求政策在整个范围内解决数字不平等问题。 Resumen: La desigualdad digital es un tema crítico en nuestra economía del conocimiento. A menudo, la desigualdad digital se enmarca como un problema que solo enfrentan las personas mayores. Esta representación bastante estereotipada puede resultar en acciones políticas improvisadas y sin éxito. El objetivo del artículo es tomar las experiencias de ciudadanos que nunca o rara vez usan las TIC como punto de partida para mostrar el impacto y los resultados de la digitalización en la vida de las personas con una posición socioeconómica baja (LSEP) y en diferentes intersecciones, como como el género, la pobreza, la etnia y la edad. Los resultados de este estudio cualitativo enfatizan que no poder usar Internet impacta negativamente en los sentimientos de pertenencia y confianza en uno mismo. Los ciudadanos necesitan invertir continuamente en equipos nuevos o diferentes y en habilidades para mantenerse al día. Las oportunidades de inversión se configuran en función del nexo de género, clase, nivel educativo y situación laboral. Al abordar la desigualdad digital, la simple formación de personas en habilidades digitales particulares es insuficiente. Mostramos que la complejidad de la desigualdad digital y su interrelación con las desigualdades sociales en términos de clase, edad, género y etnia exigen que la política aborde la desigualdad digital en todo su alcance.